Retrospective multivariable comparison for complications of third molar surgery performed under general versus local anaesthesia. (30th September 2018) - Beteramia, D.; Azami, O.; Garg, K.; Grubor, D.
Abstract: Aim: To compare the incidence of complication rates as a result of third molar surgery when performed under local versus general anaesthesia. Materials and methods: Data were collected using a combination of computer database and patient records. A total of 277 patients were included in the study (130 local anaesthesia, 147 general anaesthesia). Several variables were collected and assessed including age, gender, method of anaesthesia, radiographic grading and complications. Results: Five hundred and twenty‐three mandibular third molars were removed, 284 being removed under general anaesthesia and 239 under local anaesthesia. There were a total of 20 complications (3.8%), nine of those from procedures performed under local anaesthesia and 11 from procedures performed under general anaesthesia. There was a statistically significant increase of alveolar osteitis for procedures performed under LA. However, when assessing overall complication rate, there was no statistically significant difference in LA versus GA. Conclusions: Teeth more severely impacted or angulated tend to be removed under general anaesthesia for reasons such as surgical access and patient experience. Our study suggests there is an increase in alveolar osteitis when third molars are removed under LA. However, there was no significant correlation found between the method of anaesthesia and overall complication rate when combining all complications. The present study indicates that other variables, such as gender and age may be more important in determination of post‐surgical complication rates after wisdom teeth removal. It is therefore reasonable for clinicians and patients to base their decision for modality of anaesthesia on patient preference, surgical difficulty, medical background and economic factors.